Digitising historic excavation archives - Andrzej Prinke (Internet Archaeology, 2005)
The ARENA project gave the Archaeological Museum in Poznań an opportunity to work on the preservation and dissemination of archives of international significance in the museum's care. In addition to carrying out preservation work on digital archives two specific resources were presented: